Preliminary Investigation of Magnetic Resonance Imaging Guided Beamforming in Flexible Type Ultrasonic Array Transducers - Hasegawa, Koki; Namekawa, Kengo; Takayanagi, Shinji; Akiyama, Iwaki (Frontiers in Physics, 2021)
A flexible-shaped ultrasonic array probe that can be used in a high magnetic field environment in an MRI gantry has been developed. Given that this probe can be fixed according to the shape of the skull’s surface, it is particularly applicable for imaging in the brain. To perform ultrasonic beamforming using a bent probe, it is necessary to measure the bent shape. Therefore, in this research, the curvature of the probe was estimated using MRI. A phantom with ellipse surface close to the shape of a skull was created using a 3D printer. The probe was arranged along the phantom surface to perform MRI and ultrasonic beamforming. The ultrasonic array transducer had 192 elements made from 1-3 composite piezoelectric materials with an element spacing of 0.3 mm. Eight MR position markers were attached to the probe in parallel in two rows of four each, with the array transducer in between. The delay time of each element in dynamic focusing for reception was calculated from its position estimated by the curvature of the probe. To evaluate the feasibility of this method, a B-mode image of 0.98 mm-diameter-thread targets placed in water was generated. The beam width at half maximum of the echo peak in the lateral direction from the thread target set up near the transmission focal point was calculated based on the B-mode image. It was found that the beam width of 1.32 mm in the proposed method, which was close to the thread diameter, whereas that was 4.38 mm in the conventional method that did not consider the bending of the probe. Consequently, the proposed beamforming technique is feasible for ultrasonic imaging through an arbitrary curved surface. Practical applications with a head phantom mimicking skull and cerebral tissue are expected.